Pengabdian Masyarakat Pembuatan Website Umkm Oleh-Oleh Tiga Putri - Abdillah, Muhammad Syarif; Wulan, Nur; Sitorus, Dicky Andreas; Ramadhan, Fahmi; Pratama, Wahyu; Fauzi, Ilham; Harahap, Renaldy (Jurnal Pengabdian Masyarakat, 2025)
His study aims to develop a website for the MSME "Oleh-Oleh 3 Putri" to enhance its digital marketing. The methodology includes partner needs analysis, interface design using HTML, CSS, and JavaScript, and the implementation of basic e-commerce features such as a product catalog (20 items), a shopping cart, and a contact page. During the development phase, 100% of the partner’s needs were met based on interviews and direct observation. Internal testing demonstrated 90% ease of navigation according to evaluations by 15 users, along with an 80% improvement in the MSME owner’s knowledge in managing website content through intensive training. Although not yet officially launched, 95% positive feedback was obtained from potential customers regarding visual design and product information through a limited survey. Technical challenges such as payment integration and cybersecurity have been identified as priorities for further development. The main conclusion is that the website is ready to serve as a digital marketing tool for the MSME, with recommendations for phased implementation and ongoing technical support.